Quality of investment environment. Evidence from Romania - Felix-Constantin Burcea (European Regional Science Association (ERSA), 2012)
The aim of the present paper is to describe the investment environment in Romania, to highlight the stringent problems that need to be solved and also to propose solutions for a better investment environment. In the actual economic context, policymakers across all regions are facing difficult economic management challenges. After closing the output gap and reducing the excess capacity generated during the crisis, emerging and developing countries are benefitting from buoyant internal demand, although they are now facing inflationary pressures caused by rising commodity prices. In advanced economies, the devastating earthquake in Japan and doubts about the sustainability of public debt in Europe, US and Japan, are undermining investor and business confidence and casting a shadow of uncertainty over the short-term economic outlook. By implementing the Porter's Diamond analysis in the present paper, we can observe what is the Romanian place among the European Union concerning the country competitiveness and, therefore, the quality of the investment environment. I applied the methodology used in the Global Competitiveness Report 2011-2012, and the pillars for this analysis are: Basic Requirements (Institutions, Infrastructure, Macroeconomic stability, Health and primary education), Efficiency enhancers (Superior education and training, Goods market efficiency, Labor market efficiency, Financial market sophistication, Technological readiness, Size of market) and Factors of innovation and sophistication (Business sophistication, Innovation). To highlight the existent problems in the Romanian investment environment and to identify possible solutions for the future, I made an analysis in which Romania is compared with the average performance from EU 27 for as series of indicators from Porter's Diamond, using the data's from the Global Competitiveness Report 2011-2012, considering: the competitive advantage or disadvantage by comparing the Romanian Score with EU average; the intensity of the competitive (dis)advantage by comparing the score difference between Romania and EU average with the standard deviation of data series for each indicator. The last part of the paper is dedicated to a microeconomic model applied for the Romanian case that was developed by Abhijit Banerjee on the economy of India and published with the launch of the study "Equity and Growth in a Globalizing World" by the Commission for Growth and Development in 2010. This microeconomic model has like primary goal to determine the minimum wealth for a person required to start a business and to highlight the problems in the Romanian investment environment.
Keywords: E22; F21; L26; 330; investment environment; clusters; Porter's Diamond; competitiveness